Social stress during lactation, depressed maternal care, and neuropeptidergic gene expression. Issue 7 (October 2015) - Murgatroyd, Christopher A.; Taliefar, Mohammad; Bradburn, Steven; Carini, Lindsay M.; Babb, Jessica A.; Nephew, Benjamin C.
Abstract : Depression and anxiety can be severely detrimental to the health of both the affected woman and her offspring. In a rodent model of postpartum depression and anxiety, chronic social stress exposure during lactation induces deficits in maternal care and increases anxiety. Here, we extend previous findings by expanding the behavioral analyses, assessing lactation, and examining several neural systems within amygdalar and hypothalamic regions involved in the control of the stress response and expression of maternal care that may be mediating the behavioral changes in stressed dams. Compared with control dams, those exposed to chronic social stress beginning on day 2 of lactation show impaired maternal care and lactation and increased maternal anxiety on day 9 of lactation. Saccharin-based anhedonia and maternal aggression were increased and lactation was also impaired on day 16 of lactation. These behavioral changes were correlated with a decrease in oxytocin mRNA expression in the medial amygdala, and increases in the expressions of corticotrophin-releasing hormone mRNA in the central nucleus of the amygdala, glucocorticoid receptor mRNA in the paraventricular nucleus, and orexin 2 receptor mRNA in the supraoptic nucleus of stressed compared with control dams. The increase in glucocorticoid receptor mRNA in the paraventricular nucleus was negatively correlated with methylation of a CpG site in the promoter region. In conclusion, the data support the hypothesis that social stress during lactation can have profound effects on maternal care, lactation, and anxiety, and that these behavioral effects are mediated by central changes in stress and maternally relevant neuropeptide systems.